Small and medium-sized Transnational Corporations : executive summary and report on the Osaka Conference - Fujita, Masataka...[et al] (UN New YorkUS, 1994)
Contains an executive summary of the publication entitled 'Small and medium-sized transnational corporations' which analysed various facets of foreign direct investment and international production by these enterprises. Presents a report on the International Forum on Small and Medium-Sized Enterprises and Development, held in Osaka Japan 8-9 September 1993.